THE EFFECT OF GROSS DOMESTIC PRODUCT AND EXCHANGE RATE ON THE VOLUME OF BEEF IMPORTS FROM AUSTRALIA, INDIA, AND THE UNITED STATES IN INDONESIA FROM 2013 TO 2022 - Ristra Inez Salsabila; Eni Setyowati (SEAN Institute, 2023)
This research was conducted because the volume of beef imports from Australia, India, the United States tends to increase the most compared to other countries. The increase in demand that is not offset by domestic beef production results in the Government having to import beef from abroad, especially at most in 3 countries Australia, India, the United States. Based on this, researchers want to know the effect of Gross Domestic Product (GDP) and Exchange Rate on the Volume of Beef Imports of Australia, India, the United States both simultaneously and partially. The method used is quantitative research with data sources originating from the second party (secondary) in the form of panel data and processed using Eviews9 software.. The results of the F test can be known simultaneously The volume of the IMP is affected by GDP and Exchange Rate. The results of the t test can be seen partially, IMP is only influenced by GDP.